Sensorimotor Integration by Corticospinal System - Moreno-López, Yunuen; Olivares-Moreno, Rafael; Cordero-Erausquin, Matilde; Rojas-Piloni, Gerardo (Frontiers in Neuroanatomy, 2016)
The corticospinal (CS) tract is a complex system which targets several areas of the spinal cord. In particular, the CS descending projection plays a major role in motor command, which results from direct and indirect control of spinal cord pre-motor interneurons as well as motoneurons. But in addition, this system is also involved in a selective and complex modulation of sensory feedback. Despite recent evidence confirms that CS projections drive distinct segmental neural circuits that are part of the sensory and pre-motor pathways, little is known about the spinal networks engaged by the corticospinal tract, the organization of CS projections, the intracortical microcircuitry, and the synaptic interactions in the sensorimotor cortex that may encode different cortical outputs to the spinal cord. Here is stressed the importance of integrated approaches for the study of sensorimotor function of CS system, in order to understand the functional compartmentalization and hierarchical organization of layer 5 output neurons, who are key elements for motor control and hence, of behavior.